2015
DOI: 10.1080/19361610.2015.1004606
|View full text |Cite
|
Sign up to set email alerts
|

Causes and Incentives for Terrorism in Pakistan

Abstract: This study offers fresh empirical insights into the causes of terrorism inPakistan. The authors present a novel strategy for hypothesis building in conflict studies, and explore the importance of the explanatory variables within the time frame of the analysis. The hypothesized relationships are tested using pooled cross-section time series data from five regions of Pakistan (the federally controlled area and four provinces from 1980 to 2010) using fixed effect negative binomial regression. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Pakistan constitutes a good case to be considered for examining fiscal response to terrorism as the country has remained a victim of extensive terrorist activities. It is an undeniable fact that Pakistan has been among those countries which are always at the forefront of terrorist incidents due to various factors such as religious, geographical, ethnic, political, and economic-mainly unemployment and income inequality (Ismail & Amjad, 2014;Khan, et al, 2016;Syed et al, 2015). The incident of 9/11 has played a vital role in engorging terrorism in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan constitutes a good case to be considered for examining fiscal response to terrorism as the country has remained a victim of extensive terrorist activities. It is an undeniable fact that Pakistan has been among those countries which are always at the forefront of terrorist incidents due to various factors such as religious, geographical, ethnic, political, and economic-mainly unemployment and income inequality (Ismail & Amjad, 2014;Khan, et al, 2016;Syed et al, 2015). The incident of 9/11 has played a vital role in engorging terrorism in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…In connection with India's strengthening of the security infrastructure in Afghanistan, Pakistan's military operations on the western border have attracted Pakistan's security forces. However, the new Afghan government has removed this view by building a more friendly relationship with Pakistan, thereby reducing its geographical and historical burden [Syed, Saeed, Martin 2015].…”
Section: Basic Interests Of Pakistanmentioning
confidence: 99%
“…Callaway and Harrelson‐Stephens () studied Northern Ireland and concluded that as political openness decreases then terrorism increases (p. 683). Other case studies that attribute terrorism to political causes include Sabri () who examined Turkey's violent period in the late 1970s and Syed, Saeed, and Martin () who studied the causes of terrorism in Pakistan. Çinar (), in a theoretical piece, argues that a direct link exists between regime type and terrorism while in a much earlier work, Ross () created a model of the structural causes of terrorism which included type of political system.…”
Section: The Political Root Causes Of Terrorismmentioning
confidence: 99%